PENGARUH KONFLIK PERAN DAN KEPUASAN KERJA TERHADAP KEINGINAN BERPINDAH - Rr Tjahjaning Poerwati, Titiek Suwarti (Jurnal Ekonomi dan Bisnis Kontemporer, 2015)
This study aims to examine and analyze the role of relationship conflict and job satisfaction either partially or simultaneously to turnover intentions. The population in this study were all employees working in the Kantor Akuntan Publik (KAP) .Sampel used as many as 76 respondents. Sampling technique used is sampling conviniance convenience reasons. The results show that role conflict has a significant relationship to turnover intentions. While the job satisfaction have the opposite result which does not have a significant effect on turnover intentionsKeywords: Role Conflict, Job Satisfaction, Turnover Intentions